Language Style in a Song Lyric â€œBila Waktu Tâ€™lahBerakhirâ€ and â€œKhusnul Khotimahâ€ By Opick - Astuti, Sri Puji; Hidayah, Choirunissa Husna (Proceedings International Conference of Culture and Sustainable Development; Vol 3 (2025): PROCEEDINGS ICOCAS, 2025)
The lyrics of â€œBila Waktu Tâ€™lah Berakhirâ€ and â€œKhusnul Khotimahâ€ by Opick explore the theme of death and the afterlife. These songs employ various language style devices to convey religious and reflective messages to the listeners. To gain deeper understanding of the meanings embedded in the lyrics, a study of the figurative language used is essential. This research aims to identify and describe the types of figurative language found in the two songs. It adopts a qualitative descriptive method, with the primary data being the lyrics of Opickâ€™s songs. Data were collected through listening and note-taking techniques, followed by analysis based on language style theories. The findings reveal the use of rhetorical question, metaphors, personification, pleonasm, repetition, pleonasm, and tautology. These devices are intended to encourage listener to reflect on the meaning of life, remind them of the impermanence of the world, and emphasize the importance of doing good deeds before death arrives.
Keywords: language style, song lyric, Opick, Bila Waktu Tâ€™lah Berakhir, Khusnul Khotimah